multistrap: boosting phylogenetic analyses with structural information - Athanasios Baltzis; Luisa Santus; Björn E. Langer; Cedrik Magis; Damien M. de Vienne; Olivier Gascuel; Leila Mansouri; Cedric Notredame (Nature Communications)
Abstract In a phylogeny, trustworthy reliability branch support estimates are as important as the tree itself. We show that reliability support values based on bootstrapping can be improved by combining sequence and structural information from proteins. Our approach relies on the systematic comparison of homologous intra-molecular structural distances. These variations exhibit less saturation than sequence-based Hamming distances and support the computation of tree-like distance matrices resolvable into phylogenetic trees using distance-based methods such as minimum evolution. These trees bear strong similarities to their sequence-based counterparts and allow the estimation of bootstrap support values, but they are sufficiently distinct so that their information content may be combined. The combined sequence and structure bootstrap support values yield improved discrimination between correct and incorrect branches. In this work we show that our approach, named multistrap, is suitable for the improvement of bootstrap branch support values using both predicted and experimental 3D structures.